Invasive Round goby Neogobius melanostomus distribution, relative abundance, and establishment in pools of the Illinois Waterway following 30 years of invasion - Brandon S. Harris; Michael J. Spear; Andrya L. Whitten; Eric C. Hine; Allison W. Lenaerts; Andrew T. Mathis; Kristopher A. Maxson; Madison Myers; Melissa Oubre; Samuel J. Schaick; Levi E. Solomon; Andrew T. Wieland; et al. (Journal of Freshwater Ecology, 2024)
Round goby Neogobius melanostomus – a small, benthic fish native to Eurasia – was first introduced to North America in the 1980s through ballast water of cargo ships. In 1990, the Round goby was first discovered in the Laurentian Great Lakes Basin and rapidly spread through all Great Lakes from 1993 to 1998. The Round goby is an aggressive, prolific, and efficient egg predator that subsequently displaced native fishes from their preferred habitats and resources in the Great Lakes, where they are well established and abundant. From Lake Michigan, Round goby moved south into the Chicago Area Waterway System in 1993 and slowly progressed down the Illinois Waterway to the Mississippi River from 2004 to 2019, where less is known about their abundance, establishment, and impact. The goal of this study was to gain a comprehensive understanding of the first large river invasion by Round goby in the Mississippi River Basin by leveraging Round goby capture data from 2019 to 2022 on all pools of the Illinois Waterway. We describe their current distribution, relative abundance (i.e., catch-per-unit-effort), frequency of occurrence, and establishment (i.e., presence of young-of-year and adults) status throughout the Illinois Waterway. Results show that catch-per-unit-effort, frequency of occurrence, and the proportion of sites where multiple life stages are present are considerably higher in the upstream pools relative to more downstream pools of the Illinois Waterway. Our data support that the Round goby has established self-sustaining populations in the Chicago Area Waterway System, the upper Illinois River (i.e. Dresden Island Pool downstream through Starved Rock Pool), and a portion of the lower Illinois River (i.e. Peoria Pool downstream through Alton Pool) of the Illinois Waterway. In the lower Illinois River, Round gobies appear to only be established in Peoria Pool, with captures occurring infrequently in La Grange Pool, and no Round gobies being captured in Alton Pool.